The Grammatical Error Analysis of Students’ Speaking Performance - Cut Mawar Helmanda; Siti Safura; Evi Suriadi (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The aims of this study were to investigate the types of grammatical errors in students’ speaking performances, the factors that cause the grammatical errors and the difficulties faced by English department students in speaking. The data were collected through observation and interview. The sample of this study was 10 students of English department at Tarbiyah Faculty of Muhammadiyah University, Aceh. The result of this study revealed that the students made the four types of grammatical errors which classified into omission, misformation, misorder, and overgeneralization. In errors of omission, the students mostly omitted use of verbs, subject, object, prepositions, plural nouns, articles, conjunctions, superlatives form, passive verbs, and to be. In misformation type, the students made incorrect form of verbs, noun, articles, object pronoun, and chosen words. For misordering type, the incorrect placement of verbs, adjectives, nouns, and modals were committed. Last, the students overused the adverb, objects, articles, prepositions, and to be, in overgeneralization. Also, the finding indicated that interlingua and intralingua transfer are two main factors that caused students’ grammatical errors in speaking. Meanwhile, the students’ understanding of grammar and chosen vocabulary were indicated as the problems faced by students in speaking performance..